Peningkatan Literasi Teknologi Masyarakat Desa Kalijaga melalui Pelatihan Pembuatan Running Text - Muhammad Qusyairi; Arnila Sandi; Bahtiar Bakti (Universitas Hamzanwadi, 2026)
The development of information technology requires communities to have adequate technological literacy to be able to adapt to the demands of the digital era. However, rural communities still face limitations in utilizing information technology that is applicable and easy to implement. This community service activity aims to improve the technological literacy of the people of Kalijaga Tengah Village through training in the creation and operation of LED-based running text as a village information medium. This activity involved 25 participants consisting of village officials and the general public. The implementation method of the activity included preparation, socialization, practice-based training, evaluation, and follow-up. Evaluation was carried out through direct observation and a comparison of participants' levels of understanding before and after the training. The results of the activity showed a significant increase in participants' understanding of the functions, components, and operation of LED-based running text, with an average increase in understanding reaching more than 60%. This activity contributed to encouraging technological independence of village communities and the sustainable use of simple technology to support the effectiveness of village information dissemination.